Plan de marketing para el posicionamiento empresarial del Restaurante Delicias del Negro, en la ciudad de Guaranda, provincia Bolívar, año 2023. - Camacho Puente, Hithler Adonnis (2023)
In the present research project, a Marketing Plan is carried out for the business positioning of the Delicias del Negro restaurant, in the city of Guaranda, Bolívar province, year 2023. The restaurant in which the research was carried out did not have any marketing plan, that is, they had a good menu, new and innovative dishes with characteristics from other provinces of Ecuador, but unfortunately they did not know how to reach the Guarandeña citizens. For this reason, the general objective of our research was established to determine the incidence of a Marketing Plan for the business positioning of the Delicias del Negro restaurant, in the city of Guaranda, Bolívar province, year 2023. To achieve it, different types of research were used: exploratory research, documentary research, descriptive research, field research, qualitative research, and quantitative research, which helped us to know with more certainty the state of the restaurant and then proceed. with the respective surveys of a sector of the citizens of the city of Guaranda and proceed with the survey of Mr. Raul Güingla, owner and founder of the Delicias del Negro restaurant. The research project is highly feasible and effective for the restaurant since highly satisfactory results were achieved through the use of technological tools such as social networks.